Synthesis and trypanocidal activity of salicylhydrazones and p-tosylhydrazones of S-(+)-carvone and arylketones on African trypanosomiasis - Bienvenu GLINMA , , , Fernand A. GBAGUIDI , , , Urbain C. KASSEHIN, Salomé D.S. KPOVIESSI, Alban HOUNGBEME, Horrhus D. HOUNGUE, Georges C. ACCROMBESSI and Jacques H. POUPAERT (Journal of Applied Pharmaceutical Science, 2015)
Hydrazones are nowadays considered to be good candidates for various pharmaceutical applications. Here, we have synthesized two series of hydrazones: salicylhydrazones (GS1-4) and p-tosylhydrazones (GT1-4) from S-(+)-carvone and three aryketones with good yields (57-91%). Molecules were characterized by elemental analyses; TLC, NMR 1H, NMR 13C and MS. Submitted, in vitro, to their antiparasitic testing on Trypanosoma brucei brucei, and toxicity on Artemia salina Leach, all compounds except GT2 showed significant antitrypanosomal activity IC50 ranging from 1 to 34 micromolar (µM). Among them, 2-acetynaphthalene salicylhydrazone GS4 (IC50 = 1.97 ± 0.42 µM) and 7-methoxy-1-tetralone p-tosylhydrazone GT3 (IC50 =7.98 ± 1.65 µM) exhibited good trypanocidal activity and the other are moderates on parasite; when the compounds GS1, GT3 and GT4 presented toxic activity on larvae. In agreement to their selectivity index, which is greater than 1 (SI > 1), products turn out quite selective on the parasite: a series of salicylhydrazones revealed more selective (SI ≥ 11), especially GS4 (SI = 157) than the series of p-tosylhydrazones showed 1 ≤ SI ≤ 22. The synthesized compounds clearly displayed significant selective pharmaceutical activities on the parasite tested. Compounds developing could open promising route to news drug-candidates.
Keywords: Salicylhydrazones, p-tosylhydrazones, trypanocidal activity, selectivity index.